2004
DOI: 10.1177/147323000403200512
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Teicoplanin in the Treatment of Neonatal Staphylococcal Sepsis

Abstract: We aimed to evaluate retrospectively the clinical and bacteriological efficacy and potential side-effects of teicoplanin treatment in neonates with proven staphylococcal infection. There were 37 episodes of staphylococcal septicaemia in neonates with a mean gestational age of 34.2 ± 2.3 weeks; 26 were caused by coagulasenegative staphylococcal (CoNS) sepsis and 11 by Staphylococcus aureus sepsis. All episodes were treated with teicoplanin (intravenous loading dose 16 mg/kg followed by a maintenance dose of 8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Several studies have shown that teicoplanin is as effective as vancomycin in the treatment of bacteremia, bone and joint infections and is generally better tolerated with fewer adverse events [109111]. Teicoplanin is available for intravenous or intramuscular administration and has an advantage in terms of its single daily dosing.…”
Section: Treatment Of Mrsamentioning
confidence: 99%
“…Several studies have shown that teicoplanin is as effective as vancomycin in the treatment of bacteremia, bone and joint infections and is generally better tolerated with fewer adverse events [109111]. Teicoplanin is available for intravenous or intramuscular administration and has an advantage in terms of its single daily dosing.…”
Section: Treatment Of Mrsamentioning
confidence: 99%
“…In children, the oral dose is 100 to 200 mg twice-daily and the intravenous dosage consists in a loading dose of 12 mg/kg twice-daily followed by a maintenance dose of 12 mg/kg once-daily [3]. Teicoplanin has been found efficacy and safety in infants and children [4][5][6][7][8]. Teicoplanin has been found efficacy in infants with staphylococcal sepsis [4].…”
Section: Discussionmentioning
confidence: 99%
“…Teicoplanin has been found efficacy and safety in infants and children [4][5][6][7][8]. Teicoplanin has been found efficacy in infants with staphylococcal sepsis [4]. Teicoplanin and vancomycin are equally effective in treating children with bacterial infections but the incidence of toxicity and other adverse-effects are lower with teicoplanin [5,6].…”
Section: Discussionmentioning
confidence: 99%